2019
DOI: 10.1242/bio.042176
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of fruit-fly eclosion rhythms evolves by strengthening circadian gating rather than developmental fine-tuning

Abstract: Fruit flies (Drosophila melanogaster) eclose from their pupae mainly around dawn. The timing of eclosion is thought to confer adaptive benefits to the organisms and thus shows remarkable accuracy. However, it is not clear what factors are involved in the evolution of such accuracy in natural populations. In this study, we examined the relative contributions of gating of eclosion by the circadian clock versus clock-independent developmental rates and light-induced responses in the eclosion phenotype exhibited b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Similar to adult emergence, embryo hatching is also considered to be a “gating” process (Mark et al, 2021; Varma et al, 2019; Villamizar et al, 2013). The role of the clock is defined as a gated switch, by which the clock imposes a daily rhythm on the embryo/adult during the gated period, initiating the hatching/emergence process (Myers, 2003; Qiu & Hardin, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to adult emergence, embryo hatching is also considered to be a “gating” process (Mark et al, 2021; Varma et al, 2019; Villamizar et al, 2013). The role of the clock is defined as a gated switch, by which the clock imposes a daily rhythm on the embryo/adult during the gated period, initiating the hatching/emergence process (Myers, 2003; Qiu & Hardin, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is worth highlighting that these data refer to pupariation time, and not eclosion. Thus, it is still possible that both s-tim and ls-tim homozygous flies maintain a circadian rhythm in eclosion, differentially regulating the timing of the final steps of metamorphosis and/or circadian gating of eclosion ( Varma et al, 2019 ; Mark et al, 2021 ). Further, we hypothesize that the identified delay might be instrumental to prolong larval feeding and thus the growth phase, resulting in larger flies, a trait which is strongly selected at higher latitudes ( Chown and Gaston, 2010 ; Stillwell, 2010 ), and is a feature of diapause-destined individuals in several insect species ( Hahn and Denlinger, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, dTet has been shown to be required during embryonic and larval stages in PDF neurons to ensure proper circadian behavior in adult flies ( Wang et al, 2018 ). In fact, the circadian rhythm also modulates the timing of preadult developmental events in Drosophila ( Yadav et al, 2014 ; Varma et al, 2019 ) and thus, defects in the circadian clock might contribute to the observed lethality.…”
Section: Discussionmentioning
confidence: 99%